2
$\begingroup$

Known that $\sum_{n=0}^{\infty}{x^n}{z^n}=\frac{1}{1-xz}$. If we have $\sum_{n=0}^{\infty}\frac{{x^n}{z^n}}{n\beta + \alpha}$ where $\beta, \alpha $ are element of real numbers but not equal $0$. What is a suitable expression for that summation?

$\endgroup$
  • $\begingroup$ This question is not very clear-at least to me. $\endgroup$ – picakhu Nov 23 '11 at 17:01
  • 2
    $\begingroup$ Why you don't just replace $xz$ by (say) $t$ so that the question is simpler? (this does not answer it, mind you). $\endgroup$ – leonbloy Nov 23 '11 at 17:02
  • $\begingroup$ Do you know the answer when $\alpha = 0$? $\endgroup$ – Qiaochu Yuan Nov 23 '11 at 17:06
  • 1
    $\begingroup$ Also, what are $\alpha$ and $\beta$? $\alpha$ had better be nonzero, if you're going to avoid a zero denominator in the first term. $\endgroup$ – Dimitrije Kostic Nov 23 '11 at 17:06
  • $\begingroup$ @picakhu: i just want to find the suitable equation for related summation. $\endgroup$ – DRN Nov 23 '11 at 17:06
4
$\begingroup$

Since $x$ and $z$ only occur as a product, denote $w = x z$. We seek to evaluate $ f(w) = \sum_{n=0}^\infty \frac{w^n}{\beta n + \alpha}$.

Notice that $\frac{w^n}{n \beta + \alpha} = \frac{1}{\beta} w^{-\frac{\alpha}{\beta}} \int w^{n - 1+ \frac{\alpha}{\beta}} \mathrm{d} w$. Therefore $$ f(w) = \frac{1}{\beta} w^{-\frac{\alpha}{\beta}} \int_0^w \frac{z^{\frac{\alpha}{\beta}-1}}{1-z} \mathrm{d} z + \frac{c}{\beta} w^{-\frac{\alpha}{\beta}} $$ The constant $c$ is determined by setting $\alpha = \beta$. Then, using the series, $f(w) = \frac{1}{\beta w} \sum_{n=0}^\infty \frac{w^{n+1}}{n+1} = -\frac{1}{\beta w} \log(1-w)$.

So we get: $$ -\frac{1}{\beta w} \log(1-w) = \frac{1}{\beta w} \int_0^w \frac{1}{1-z} \mathrm{d} z + \frac{c}{\beta w} $$ From where it follows that $c=0$. Therefore the sum admits the following integral representation: $$ f(w) = \frac{1}{\beta} w^{-\frac{\alpha}{\beta}} \int_0^w \frac{z^{\frac{\alpha}{\beta}-1}}{1-z} \mathrm{d} z = \frac{1}{\beta} \int_0^1 \frac{u^{\frac{\alpha}{\beta}-1}}{1-w u} \mathrm{d} u = \int_0^1 \frac{u^{\alpha-1}}{1- w u^\beta} \mathrm{d} u $$ This integral define a special function, known as Lerch zeta function.


Actually the question from Didier Piau, made me realize that I missed a simpler route: $$ f(w) = \sum_{n=0}^\infty \frac{w^n}{\beta n +\alpha} = \sum_{n=0}^\infty w^n \int_0^1 u^{n \beta + \alpha-1} \mathrm{d} u = \int_0^1 \frac{u^{\alpha-1}}{1-w u^\beta} \mathrm{d} u $$

$\endgroup$
  • $\begingroup$ The computation of $c$ is odd. All one knows is that for every $(\alpha,\beta)$ there is some $c_{\alpha,\beta}$ such that $f(w)$ is so and so, and you show that $c_{\alpha,\alpha}=0$ for every $\alpha$. Right. But this seems to give no information at all on $c_{\alpha,\beta}$ for $\alpha\ne\beta$. $\endgroup$ – Did Nov 24 '11 at 7:41
  • $\begingroup$ @DidierPiau Yes, but I can justify $c_{\alpha,\beta} = 0$ a-posteriori, by rexpanding the integrand. I have expanded the answer. Of course, the integral representations in my post work for $\frac{\alpha}{\beta}>0$. $\endgroup$ – Sasha Nov 24 '11 at 16:02
  • $\begingroup$ thanks all.. any other ways to find the expression instead of using Lerch zeta function? $\endgroup$ – DRN Nov 25 '11 at 6:34
  • 1
    $\begingroup$ @Norlyda Not for generic $\alpha$, $\beta$. Notice, though, that for $\alpha = \beta/2$, $f(w) = \frac{2}{\beta \sqrt{w}} \arctan(\sqrt{w})$. $\endgroup$ – Sasha Nov 25 '11 at 6:40
  • $\begingroup$ @Sasha: my task is actually to form that summation in form of this expression, $\sum_{n=0}^{\infty}{x^n}{z^n}=\frac{1}{1-xz}$, maybe it is impossible,right? $\endgroup$ – DRN Nov 25 '11 at 7:35
5
$\begingroup$

$$\sum\limits_{n=0}^{+\infty}\frac{x^n}{n\beta+\alpha}= \frac1{\beta x^{\alpha/\beta}}\int\limits_0^{x}\frac{u^{\alpha/\beta}}{1-u}\frac{\mathrm du}u $$

$\endgroup$
4
$\begingroup$

$$\sum_{n=0}^{\infty}\frac{{x^n}{z^n}}{n\beta + \alpha}$$

is expressible in terms of the Lerch transcendent:

$$\Phi(z,s,a)=\sum_{k=0}^\infty \frac{z^k}{(a+k)^s}$$

Taking $s=1$ gives

$$\Phi(z,1,a)=\sum_{k=0}^\infty \frac{z^k}{a+k}$$

after which

$$\begin{align*}\Phi(xz,1,a)&=\sum_{k=0}^\infty \frac{(xz)^k}{a+k}\\ \Phi(xz,1,\alpha/\beta)&=\sum_{k=0}^\infty \frac{(xz)^k}{\alpha/\beta+k}\\ \frac1{\beta}\Phi(xz,1,\alpha/\beta)&=\sum_{k=0}^\infty \frac{(xz)^k}{\alpha+\beta k}\end{align*}$$

and presto!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.